WORK FAMILY CONFLICT CIRCLES AND THEIR IMPACT ON WORKPLACE DEVIANCE FOR WORKING COUPLES - Sayyida Sayyida; Nindria Untarini (Media Mahardhika, 2020)
Gender equality and the necessities of life in this era require many couples working both husband and wife. This has an impact on work family conflicts resulting from an imbalance between work and family responsibilities. This research aims to review various references related to work family conflict perceived by the working couples and their effect on production deviance. The results of the review indicate the existence of work family conflict circles that occur in workers ie work family conflict incumbent influenced by work family conflict partner and work family conflict incumbent and partner influenced by work family conflict leader. and than work family conflict have impact on production deviance moderated by age and gender.